Structure and properties of nanoscale materials: theory and atomistic computer simulation. (7th February 2012) - Bichara, C.; Marsal, P.; Mottet, C.; Pellenq, R.; Ribeiro, F.; Saúl;, A.; Tréglia, G.; Weissker, H.–Ch.
We present a review of a few research topics developed within the "Theory and Atomistic Computer Simulation" Department at CINaM. The bottom line of the scientific activity is to use up–to–date theoretical and computer simulation techniques to address physics and materials science problems, often at the nanometric scale, in close contact with experimental groups. It ranges from the study of the structure and properties of molecular systems for organic electronics to metallic clusters and alloys, magnetic oxides, nuclear fuels and carbon–based nanostructures. These studies are motivated by fundamental research questions as well as more applied goals including environmental and energy issues, or information technologies. This broad spectrum of activities requires a large range of techniques, from theory and ab initio calculations to semi–empirical models incorporated in Monte Carlo or molecular dynamics simulations.